¿Es posible un gobierno de los jueces? - Falcón y Tella, María José (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2008)
In this article, conscientious objection and the possibility of applying it to the case of judges is studied. Given that they are specially qualified appliers of law, and that they are bound by subjection to law, their right to conscientiously object raises various issues which this paper deals with. It also looks at the characteristics of conscientious objection in contradistinction to those of civil disobedience. En alemán: Im vorliegenden Artikel geht es um die Gewissensfreiheit und ob man Sie auf die Arbeit der Richter ausdehnen kann:, da die Richter als Gesetzesanwender dem Gesetz unterworfen. Gleichfalls werden die Grundlagen der “Verweigerung aus Gewissensgründen” im Zusammenhang mit der juristischen Figur des zivilen Ungehorsams betrachtet.
Keywords: Conscientious objection; Civil disobedience; Judges; Legal realism; Verweigerung aus Gewissensgründen; Richter; Juristische Realität